Technology transfer of pepper grinders to farmer groups in Salo Palai Village, Kutai Kartanegara - Zainal Arifin; Faisyal Faisyal; Dwi Cahyadi (Universitas Muhammadiyah Magelang, 2021)
The economy of Salo Palai Village local communities, Muara Badak District, Kutai Kertanegara Regency, relies on plantations, livestock and marine and land fisheries. One of the superior plantation products in Salo Palai Village is pepper commodity. However, there are problems faced including the method of processing pepper is traditional, lack of technology and does not consider quality and cleanliness standards. To reach the world market, it is necessary to pay attention to the quality requirements and consumer tastes. For this reason, the community service aims to improve the quality of pepper in terms of post-harvest processing through assistance in the use of pepper grinders in order to produce pepper powder that provides added value and meets established quality standards. This community service is carried out with workshops covering technology transfer and assistance in the use of pepper grinders, which are expected to open new knowledge and skills for farmers. The results obtained that the local community of Salo Palai Village were able to operate a pepper grinder and were able to produce pepper powder in accordance with the quality standards.